The effect of Motivation, Organization Culture to performance of Anti-corruption Instructor with certification as Intervening variable - Novianthi, Dian; Ahmad Badawi Saluy; Novawiguna K (Dinasti Publisher, 2023)
The purpose of this study to determine and analyze the effect of motivation, organization culture to performance of anti corruption instructor with certification as an intervening factor. This research was explanatory research with survey research design. This is a survey-based research study. Primary and secondary data were used in this study. Primary data were gathered via questionnaire with Likert Scale. Motivation, Organization Culture, certification and performance are considered variables for this study. Sample size is (n 250); therefore, descriptive statistics, correlation analysis and PLS analysis have been used. Based on the analysis of the research results, it can be concluded that partially each variable, namely motivation, organizational culture has proven to have a significant effect on certification. That partially, motivation and organizational culture proved to have a positive and significant effect on performance. The conclusion is that motivation is proven to have a significant effect on performance through certification and organizational culture is proven to have a positive and significant effect on performance through certification.